Post-match Recovery Practices in Professional Football: Design, Validity, and Reliability of a New Questionnaire - Querido, Sérgio M.; Brito, João; Figueiredo, Pedro; Carnide, Filomena; Vaz, João R.; Freitas, Sandro R. (Frontiers in Sports and Active Living, 2021)
Introduction: Although several approaches have been proposed to mitigate post-match fatigue, few studies have been conducted in team sports to understand the types of recovery methods and the underlying reasons for the choices of medical and technical staff. This study aimed to develop a valid and reliable online questionnaire to assess the recovery practices implemented by football clubs within 72 h post-match. Methods: Two research members developed the original questionnaire proposal, and two experts in sports science and sports medicine confirmed the content and face validities. Then, 20 football coaches (age: 39.4 ± 6.8 years) with a minimum of 5 years of experience in professional football (9.1 ± 4.9 years) and with an academic background participated in determining the ecological validity and reliability of the questionnaire. The acceptability and relevance of the questionnaire were determined using descriptive statistics. Results: After confirming the content and face validities, one questionnaire section with two questions was excluded due to lack of relevance, seven open-ended questions were removed due to the adherence of small participants (i.e., 45.4%), and one section was divided into three to facilitate clearness in reading. The remaining sections were considered acceptable and relevant (>94.1%). About 91.8% of nominal and ordinal items derived from the questionnaire questions showed good to very good reliability outcomes (average k classification: 0.73 ± 0.13; min–max: 0.22–1.00, p < 0.05; average wk classification: 0.82 ± 0.15; min–max: 0.22–1.00, p < 0.05). Conclusions: This study provided a novel, valid, reliable, and easy-to-use tool to examine the post-match recovery practices in professional football contexts.